Answer:
Explanation:
The equation is 7(2x-1) - 11 = 6 + 6x
The equation is a linear equation because the highest power of x is one.
x is the variable and the numbers not containing x are constants
To solve the equation,
First step is to distribute. This involves opening up the bracket.
7(2x-1) - 11 = 6 + 6x will become
7×2x - 7×1 - 11 = 6 + 6x
14x - 7 - 11 = 6 + 6x
Next step is to combine like terms
14x -18 = 6 + 6x
Next step is to move the variable terms to the left hand side of the equation and move the constant terms to the right hand side of the equation. It becomes
14x - 6x = 6 + 18
8x = 24
x = 24/8 = 3